Impact of myocardial bridge on lesion morphology and clinical outcomes in patients undergoing IVUS-guided PCI for LAD CTO - Xi Wu; Mingxing Wu; Haobo Huang; Zhe Liu; He Huang; Lei Wang (Frontiers in Cardiovascular Medicine)
IntroductionMyocardial bridge (MB) is increasingly recognized for its potential role in coronary artery disease. However, its impact on lesion morphology and clinical outcomes in patients with left anterior descending (LAD) chronic total occlusion (CTO) undergoing intravascular ultrasound (IVUS)-guided percutaneous coronary intervention (PCI) remains unclear.MethodsThis single-center retrospective study analyzed 256 patients who underwent IVUS-guided PCI for LAD CTO between 2016 and 2022. Patients were divided into MB (n = 61) and non-MB (n = 195) groups based on IVUS findings. Lesion characteristics, stent strategy, and 2-year clinical outcomes were compared.ResultsMB was identified in 23.8% of patients. Compared with the non-MB group, MB patients had significantly shorter CTO length (17.71 mm vs. 21.31 mm, P < 0.001), less calcification (29.5% vs. 47.7%, P = 0.018), and more proximal lesion distribution (41.0% vs. 20.0%, P = 0.001). Despite these favorable anatomical features, the MB group had higher rates of major adverse cardiovascular events (MACE) (19.7% vs. 8.7%, P = 0.033) and clinically driven target lesion revascularization (18.0% vs. 6.7%, P = 0.016). MB was an independent predictor of MACE (HR = 2.173, P = 0.021).DiscussionMB is associated with distinct morphological features and worse clinical outcomes in LAD CTO patients undergoing PCI. Its presence may require careful procedural planning and personalized revascularization strategies to reduce long-term risks.